Atrial fibrillyatsiya - Kuchiboyev Samandar Ismatilla o‘g‘li; Sharopova Charosxon Sherzodovna; Parmonova Iroda Ulug‘bek qizi; Abdurashidova Iroda Zoyir qizi (Zien Journals, 2025)
This article discusses the classification, etiology, pathogenesis, clinical features, diagnostic methods, and treatment approaches of atrial fibrillation
Keywords: Atrial fibrillation; dyspnea; palpitations